New possibilities of using perampanel in children. Efficacy and tolerability of perampanel in the treatment of epilepsy (literature review and experience of Svt. Luka’s Association of Medical Institutions) - K. Yu. Mukhin; O. A. Pylaeva; M. Yu. Bobylova; L. Yu. Glukhova (Русский журнал детской неврологии, 2024)
Aim. To assess the efficacy and tolerability of perampanel as an additional therapy in epilepsy patients treated in St. Luke Association of medical institutions (including Svt. Luka’s Institute of Child Neurology and Epilepsy / Svt. Luka’s Institute of Pediatric and Adult Neurology and Epilepsy) with a focus on the order of perampanel administration (in groups of early and late additional therapy with perampanel).Materials and methods. This study included 270 patients aged 4 to 43 years (125 males and 145 females; 255 children and adolescents aged 4–18 years; 15 adult patients; mean age at the time of perampanel therapy initiation was 11.8 years) who received perampanel and for whom we managed to collect clinical data for at least 6 months.The study sample included 114 patients with structural and presumably structural focal epilepsy, 120 patients with genetic and presumably genetic epilepsy (including Dravet and Angelman syndromes, Lafora disease, mutations in genes PCDH19, PHACTR1, CDKL5, ARX, PING, SCN2A, KIAA2022, chromosomal microdeletions, etc.), and 36 patients with focal epilepsy of unknown etiology. In all patients, perampanel was used as an additional antiepileptic drug (AED), primarily in combination with valproate. The next most common AEDs were carbamazepine, oxcarbazepine, vigabatrin, ethosuximide (mainly in combination with valproate), levetiracetam, and topiramate; other AEDs were used significantly less often. Drug titration was performed in accordance with recommendations (dosage increase by 2 mg each 1–2 weeks) up to the therapeutic dose of 4–12 mg / day taken before sleep. The majority of patients received perampanel at a dose of 6 mg.Total duration of perampanel therapy varied between 4 and 11 months. Patients were divided into three groups: patients in group 1 received perampanel as a second drug in additional therapy (n = 21); patients in group 2 received perampanel as a third drug in additional therapy (n = 54); patients in group 3 received perampanel as at least forth drug in additional therapy (n = 195). Groups 1 and 2 were considered as groups of early additional perampanel therapy, whereas group 3 was considered as a group of late additional perampanel therapy.To evaluate perampanel efficacy, we measured proportions of responders (who demonstrated at least 50 % reduction seizure frequency compared to baseline, including patients in remission) and patients who achieved remission (no seizures over the last 6 months). Patients with a less than 50 % reduction in seizure frequency were considered as those with no significant effect. Patients who had no therapeutic effect or had aggravation (more frequent or severe seizures) in response to perampanel initiation or change of other AED to perampanel were considered as those with no effect or aggravation. We also assessed 6-month and 12-month retention rates. The main tolerability criteria were the number of side effects and proportion of patients who discontinued perampanel due to pronounced side effects.Results. The overall proportion of responders was 76 % (206 out of 270); 21.4 % of patients achieved remission (58 out of 270). No significant effect was observed in 19.6 % of patients (53 out of 270), while 4 % of patients (11 out of 270) had no effect or even aggravation. In group 1 (early therapy with perampanel as a second additional drug; n = 21), 8 out of 21 patients (38 %) achieved an at least 6-month remission; the proportion of responders reached 95.2 % (20 out of 21), while 1 patient had no significant effect. In group 2 (early therapy with perampanel as a third additional drug; n = 54), there were 83 % of responders (45 out of 54) and 25.9 % patients with remission (14 out of 54); 16.7 % of patients demonstrated no significant effect (9 out of 54); none of the patients had aggravation. Cumulative analysis of the data in groups 1 and 2 (early additional therapy with perampanel; n = 75) showed that the proportion of responders reached 86.7 % (65 out of 75), while the proportion of patients with remission was 29.3 % (22 out of 75). Ten out of 75 patients from groups 1 and 2 (13.3 %) had no significant effect; none of the patients had aggravation. In group 3 (late additional therapy with perampanel; n = 195), the proportion of responders and patients with remission was 72.3 % (141 out of 195) and 18.4 % (36 out of 195), respectively. Forty-three patients in group 3 (22 %) demonstrated no significant effect; 11 patients had no effect or aggravation (5.6 %).Thus, we observed significant differences in treatment efficacy between the groups of early and late additional perampanel therapy: 29.3 % vs 18.4 % of patients with remission and 86.7 % vs 72.3 % of responders in early and late therapy groups, respectively.Although perampanel was initiated late in the majority of patients (as forth or subsequent AED used) due to the existing recommendations and, therefore, groups of early and late additional therapy differed significantly in the number of patients, our findings predict a significant increase in perampanel efficacy if it is initiated as an early additional therapy.Of note, despite the fact that the majority of patients started to receive perampanel late, the overall perampanel efficacy was relatively high as demonstrated by 76 % of responders and 21.4 % of patients with remission.Perampanel was characterized by good tolerability, which did not differ between the groups. A total of 129 out of 270 patients (47.8 %) reported side effects, most of them were mild or moderate. Importantly, 80 cases of side effects were considered desirable, including improved sleep (sedative effect of perampanel in combination with taking the drug before bedtime) and decreased muscle tone (45 % of parents of children with cerebral palsy reported decreased spastic hypertension in their children). The most common side effects included drowsiness, lethargy, decreased muscle tone, dizziness, and decreased appetite. We observed no cases of pronounced cognitive impairments related to perampanel. Behavioral side effects, such as aggression, excitability, and behavioral disorders, were registered in 22 patients (8.14 %) and were considered the most problematic. In 7 patients, these side effects were mitigated by perampanel dose reduction. Perampanel was discontinued in 15 patients (5.5 %) due to behavioral side effects, including 2 patients (0.7 %) who developed psychosis and one patient (0.37 %) with panic attacks and episodes of derealization.The 6-month and 12-month perampanel retention rates were 85.2 % (230 out of 270) and 75.9 % (205 out of 270), respectively.Conclusion. Perampanel is highly effective in patients with genetic and structural focal epilepsy, regardless of their age. Perampanel is characterized by a convenient mode of administration (once a day, before bedtime) simple slow titration mode, and is well tolerated during long-term therapy. Our results suggest that perampanel is significantly more effective if initiated early (as early additional therapy) at an earlier disease stage before the development of pharmacoresistance. We observed significant differences in perampanel efficacy between the groups of early and late therapy. We found that perampanel was highly effective in patients with some forms of genetic epilepsy.Perampanel should be used not only in patients with drug-resistant epilepsy, but also as an additional drug in comprehensive therapy, which will lead to an improved treatment efficacy and better tolerability.